Pengaruh Struktur Kepemilikan dan Ukuran (Size) Perbankan Terhadap Kinerja Perbankan 2009-2014 - Henny Ritha (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2016)
The ownership structure and size is an important part of long-term survival of banking industry, both of which can affect  the quality of manager (agent) to manage a bank, and encourage shareholders (principals) to manage banking operations in order to improve the performance of the banking system.This study is conducted to analyze the effect of Ownership Structure and size of banks on banks performance. Both Ownership structure which is represented by Institutional Ownership and Managerial Ownership and.size are independend variables, with Return On Equity is used as a proxy for performance valuation. This study used 6 samples of banks listed in Indonesian Stock Exchange for the period 2009-2014. Technique analysis used panel data regression analysis with Microsoft Excel 2003 data processing and Eviews.8. From the results of the panel data processing, the Common Effect Model approach is obtained as the best model for estimating panel data regression model. The research proves that managerial ownership and banks size  have significant impact on banks performance, meanwhile institutional ownership has no significant impact on banks performance. Simultaneously, the three variables have a significant effect and contributed 63.07 percent to the banks performance in Indonesian Stock Exchange from 2009 to 2014, meanwhile the remaining 36,93 percent is  influenced by other variables.Researcher suggests prolonging the research period, extending the sample criteria and increasing the ownership structure of foreign ownership, the government and society as well as adding the variable of Price Earning Ratio (PER) as a proxy for banking performance.